KEBUTUHAN SPIRITUAL PADA PASIEN KANKER : LITERATURE REVIEW - ADIRATNA SEKAR SIWI (Viva Medika, 2020)
ABSTRACT Cancer is a disease that occurs due to the growth of an abnormal mass of body tissue cells that cannot be controlled, and can affect the surrounding organs. Physical problems, psychological problems, and spiritual problems are the impact of cancer. Spiritual needs can increase the individual's capability when solving the disease, and can shorten the recovery time apart from the therapy being undertaken. The purpose of this research is toknow the spiritual needs of cancer patients. Method this research uses a literature study method or literature review, and the PICOS framework is an approach to obtaining articles in this study, with data sources obtained from search engines, namely Google Schoolar, NCBI (Pubmed), Garuda and SINTA. The criteria for the journal to be reviewed are research journal articles with the subject of cancer patients about their spiritual needs with a period of journal publication in 2014-2020. The search for literature was carried out in April - July 2020. The results of this study found that the spiritual needs of cancer patients are worship, praying for their illness (praying for themselves, praying with others, and being prayed for by others) reading the Al-Qur’an. , reading the dhikr, forgive, find peace, nurse spiritual encouragement, looking for meaning and purpose in life, trying to live beside his illness, the need for peace, and seeing other people happy. Conclusion: in this study the religious dimension (Religion) was chosen by cancer patients as the dimension of spiritual need that is most needed compared to other dimensions. then as a health worker who is near the patient, nurses are expected to be able to provide nursing care related to fulfilling spiritual needs. Keywords: Spiritual needs, Cancer patients